2020
DOI: 10.1111/tbed.13656
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the serial interval and basic reproduction number of COVID‐19 in Qom, Iran, and three other countries: A data‐driven analysis in the early phase of the outbreak

Abstract: The most common routes of transmission in these outbreaks are person-to-person transmission. However, the recently published literature suggested that the COVID-19 was more contagious than previous coronavirus outbreaks, SARS-CoV and MERS-CoV (Bai, Nie, & Wen, 2020; Li et al., 2020a; de Wit, van Doremalen, Falzarano, & Munster, 2016). The basic reproduction number (R 0), as the average number of secondary infections produced by an infected case in an entirely susceptible population (Ferguson,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
4
29
0
1
Order By: Relevance
“…This is consistent with recent studies conducted in Wuhan, China, as well as in the UK, that respectively estimated an 85% and 74% reduction in the average number of daily contacts under physical distancing interventions [15,16]. This is also in line with the results of Khosravi et al and Aghaali et al, who reported a gradual decrease in Rc over time in Shohroud and Qom (central Iran) [12,17]. The gradual decrease in Rc observed in our study is promising and further highlights the possible effectiveness of NPIs implemented in Iran.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with recent studies conducted in Wuhan, China, as well as in the UK, that respectively estimated an 85% and 74% reduction in the average number of daily contacts under physical distancing interventions [15,16]. This is also in line with the results of Khosravi et al and Aghaali et al, who reported a gradual decrease in Rc over time in Shohroud and Qom (central Iran) [12,17]. The gradual decrease in Rc observed in our study is promising and further highlights the possible effectiveness of NPIs implemented in Iran.…”
Section: Discussionsupporting
confidence: 93%
“…The authors make the point that estimations based on household clusters may be 20% shorter than the true value of the serial interval. ► A number of authors, including Mettler et al, 40 Kwok et al 15 and Aghaali et al 20 highlighted the possibility of right truncated selection bias, that is, the possibility of infector-infectee pairs with longer serial intervals being under-represented in the sample due to short investigation period. Measures were taken in a number of studies to minimise this possibility.…”
Section: Methods Used For Estimating the Serial Interval And The Genementioning
confidence: 99%
“…District level R 0 estimates are more likely to show pronounced fluctuations than state or national estimates, as the latter are aggregated across a wide range of epidemiological settings. Because district-level R 0 estimates were not available from India, we compared our findings with those from the cities of Qom and Shahroud in Iran [ 29 , 30 ]. Similar to these cities, Jodhpur showed a trend of high values of R 0 in the first 14-30 days, with a subsequent decrease toward 1 [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because district-level R 0 estimates were not available from India, we compared our findings with those from the cities of Qom and Shahroud in Iran [ 29 , 30 ]. Similar to these cities, Jodhpur showed a trend of high values of R 0 in the first 14-30 days, with a subsequent decrease toward 1 [ 29 , 30 ]. The initially high R 0 values can be attributed to the suddenness of the outbreak if the surveillance system is robust.…”
Section: Discussionmentioning
confidence: 99%